A "no‐touch‐technique" in mandibular reconstruction with reconstruction plate and free flap transfer. Issue 2 (16th March 2015) - Fujiki, Masahide; Sakuraba, Minoru; Miyamoto, Shimpei; Nagamatsu, Shogo; Hayashi, Ryuichi
Abstract : Objective: Mandibular reconstruction with a mandibular reconstruction plate (MRP) and free flap transfer can involve serious plate‐related complications. The aim of our study is to present our new "no‐touch‐technique" which keeps an MRP not contaminated to saliva during the entire operation for the reduction of plate‐related complications. Patients and Methods: Data were retrospectively collected on 29 patients who had undergone segmental mandibulectomy for head and neck tumor and mandibular reconstruction with an MRP and free flap transfer from 2004 to 2013; 12 patients were reconstructed with our no‐touch‐technique from 2010 to 2013 (no‐touch‐technique group), and 17 patients with the conventional technique from 2004 to 2009 (conventional group). A rectus abdominis musculocutaneous flap or anterolateral thigh flap was transferred in all patients. The rates of perioperative recipient site complications including total flap necrosis, partial flap necrosis, wound infection, fistula formation and wound dehiscence, and reoperation for complications were compared between the groups. Results: All flaps were successfully transferred although one venous thrombosis formation occurred in the conventional group. The rate of wound infection in the no‐touch‐technique group (8.3%) was significantly lower than that in the conventional group (47.1%) ( P = 0.04). Additionally, the rate of fistula formation in the no‐touch‐technique group (8.3%) tended to be lower than that in the conventional group (29.4%) ( P = 0.35). Conclusion: The results of our study showed that our no‐touch‐technique may be a safe and effective procedure for the prevention of perioperative plate‐related complications for mandibular reconstruction with an MRP and free flap transfer. © 2015 Wiley Periodicals, Inc. Microsurgery 36:115–120, 2016.